Pengaruh Ukuran Perusahaan terhadap Kebijakan Hutang Melalui Struktur Aset Pada Perusahaan Asuransi Yang Terdaftar Di Bursa Efek Indonesia - Nurmansyah, Agung; Kristianto, Giovanny Bangun; Saraswati, Esti (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat 2025, 2025)
This study examines the effect of Firm Size on Debt Policy with Asset Structure as a mediator in insurance companies listed on the Indonesia Stock Exchange during 2016–2021. From a population of 17 firms, we obtained 14 firms with complete data (84 firm-year observations). After removing 8 statistical outliers, 76 observations remain ed for analysis. We employ path analysis at a 5% significance level. Results indicate that: (1) firm size negatively affects asset structure; (2) firm size negatively affects debt policy; (3) asset structure positively affects debt policy; and (4) asset structure mediates the effect of firm size on debt policy. These findings inform managers in balancing financing decisions with asset characteristics and regulatory capital requirements in the insurance industry.